Tinjauan Hukum Pidana Terhadap Pemalsuan Surat Berharga - Rayhan Afief Arfarizky; David Hizkia Situmorang; Sumriyah Sumriyah (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2023)
Counterfeiting of securities is a serious illegal act with the potential for significant legal consequences. The author provides an in-depth review of the criminal law aspects associated with counterfeiting securities. The aim of this research was to analyze and understand the legal framework governing counterfeiting of securities, including the criminal considerations and sanctions applied. This study also explains the concept of counterfeiting securities and how this action violates applicable law. In addition, this study also discusses the elements that must be present in an act of counterfeiting securities such as intentionality and the intention to make a profit. Furthermore, this study also analyzes the penalties and sanctions that can be applied to perpetrators of counterfeiting securities. In conclusion, this study emphasizes the importance of effective law enforcement in dealing with counterfeit securities. Perpetrators of counterfeiting securities must be held responsible for the actions that have been taken and be faced with sanctions in accordance with applicable criminal law.